ATTIRE: Albumin To prevenT Infection in chronic liveR failurE: study protocol for an interventional randomised controlled trial. Issue 10 (21st October 2018) - China, Louise; Skene, Simon S; Bennett, Kate; Shabir, Zainib; Hamilton, Roseanna; Bevan, Scott; Chandler, Torsten; Maini, Alexander A; Becares, Natalia; Gilroy, Derek; Forrest, Ewan H; O'Brien, Alastair
Abstract : Introduction: Circulating prostaglandin E2 levels are elevated in acutely decompensated cirrhosis and have been shown to contribute to immune suppression. Albumin binds to and inactivates this immune-suppressive lipid mediator. Human albumin solution (HAS) could thus be repurposed as an immune-restorative drug in these patients. This is a phase III randomised controlled trial (RCT) to verify whether targeting a serum albumin level of ≥35 g/L in hospitalised patients with decompensated cirrhosis using repeated intravenous infusions of 20% HAS will reduce incidence of infection, renal dysfunction and mortality for the treatment period (maximum 14 days or discharge if <14 days) compared with standard medical care. Methods and analysis: Albumin To prevenT Infection in chronic liveR failurE stage 2 is a multicentre, open-label, interventional RCT. Patients with decompensated cirrhosis admitted to the hospital with a serum albumin of <30 g/L are eligible, subject to exclusion criteria. Patients randomised to intravenous HAS will have this administered, according to serum albumin levels, for up to 14 days or discharge. The infusion protocol aims to increase serum albumin to near-normal levels. The composite primary endpoint is: new infection, renal dysfunction or mortality within the trial treatment period. Secondary endpoints include mortality at up to 6 months, incidence of other organ failures, cost-effectiveness and quality of life outcomes and time to liver transplant. The trial will recruit 866 patients at more than 30 sites across the UK. Ethicsanddissemination: Research ethics approval was given by the London-Brent research ethics committee (ref: 15/LO/0104). The clinical trials authorisation was issued by the medicines and healthcare products regulatory agency (ref: 20363/0350/001–0001). The trial is registered with the European Medicines Agency (EudraCT 2014-002300-24) and has been adopted by the National Institute for Health Research (ISRCTN 14174793 ). This manuscript refers to version 6.0 of the protocol. Results will be disseminated through peer-reviewed journals and international conferences. Recruitment of the first participant occurred on 25 January 2016.